Inventory dynamics and business cycles: What has changed? - Jonathan McCarthy; Egon Zakrajések (Federal Reserve Bank of New York, 2002)
By historical standards, the U.S. economy has experienced a period of remarkable stability since the mid-1980s. One explanation attributes the diminished variability of economic activity to information-technology-led improvements in inventory management. Our results, however, indicate that the changes in inventory dynamics since the mid-1980s played a reinforcing—rather than a leading—role in the volatility reduction. A decomposition of the reduction in the volatility of manufacturing output shows that it almost entirely reflects a decline in the variance of the growth contribution of shipments. And although the volatility of total inventory investment has fallen, the decline occurred well before the mid-1980s and was driven by the reduced variability of materials and supplies. Our analysis does show that since the mid-1980s, inventory dynamics have played a role in stabilizing manufacturing production: Inventory 'imbalances' are corrected more rapidly, and the quicker response of inventories to aggregate shocks—at all stages of fabrication—buffers production from fluctuations in sales to a greater extent. But more extensive production smoothing and faster dissolution of inventory imbalances appear to be a consequence of changes in the way industry-level sales and aggregate economic activity respond to shocks, rather than a cause of changes in macroeconomic behavior.
Keywords: E32; E22; D24; 330; inventories; inventory management; business cycles; GDP volatility; Lagerzyklus; Konjunktur; Volatilität; USA